Pelaporan Dana Bos UPT SPF SDI Mariso II terhadap PSAK No 45 - Rostiaty Yunus (Jurnal Aplikasi Manajemen, Ekonomi dan Bisnis, 2022)
This research aims to find out the implementation of PSAK Number 45 on the school operational assistance funds in non-profit companies, especially at UPT SPF SDI Mariso II. This research uses qualitative descriptive data analysis so that researcher can obtain detailed information about the implementation of PSAK Number 45 on the school operational assistance funds of SD INP Mariso II fund report. Based on the results of the research, it explaines that the accounting recording method is still minimal where the recording only records cash expenses and income.